Consolidation and break-up of the South American platform in southeastern Brazil: Tectonothermal and denudation histories - Hackspacher, P. C.; Ribeiro, LFB; Ribeiro, MCS; Fetter, A. H.; Hadler, J. C.; Tello, CES; Dantas, E. L. (Int Associação Gondwana Research, 2004)
The different tectonic stages that occurred at the end of the Proterozoic and during the Phanerozoic have an important bearing on the tectonothermal history of the South American Platform and its consolidation. Geochronological data (U/Pb monazite, Ar-40/Ar-39 whole rock) and apatite fission-track analysis, from Precambrian rocks of the southeastern Brazilian coastline, permit the modeling of a long-term thermal history of the crust and constrain variable denudation rates.Using these data, a temperature-time diagram reflects a period of accelerated exhumation during the end of the Brasiliano Orogeny, followed by long stability and reactivation of the platform during the Rifting Phase of the South Atlantic Ocean.U/Pb zircon and monazite (blocking temperature of ca. 650degreesC) data from a series of igneous bodies suggest that a tangential and transpressional tectonic regime occurred between 625 and 610 Ma. During the following escape tectonics, between 610 and 590 Ma the exhumation process indicates cooling rates of ca. 12degreesC/Ma. Ar-40/Ar-39 biotite ages between 540 and 510 Ma (ca. 300degreesC) and a corrected fission-track age on apatites (100degreesC) of 480 Ma indicate an exhumation event related to block tectonics with huge vertical displacement along shear zones.A long stabilization phase, with low exhumation, and cooling rate around 0.25degreesC/Ma was recorded from the Cambro/Ordovician to the Mesozoic. At 65 Ma an acceleration of the exhumation through denudation and reworking of the South American surface with cooling rate of 1.5degreesC/Ma is observed.The uplift of the Mantiqueira and Serra do Mar mountain ranges along the southeast Brazilian coastline works as a climatic barrier provoking lateral erosional processes causing long-term scarp retreat, combined with intense, but progressive denudation towards the continent. A denudation of 2.5 to 4 km was calculated for such processes. This lateral retreat of escarpments and flexural response can provide important insights regarding marginal isostatic uplift and the evolution of offshore sedimentary basins of southeast Brazil.
Keywords: thermal histories; U/Pb; denudation; Apatite Fission Track Analysis